Study of stress distribution on a circular disk by photostress analysis - Yongyut Manjit (2018)
© 2015 SPIE. Photostress analysis system was used to study the stress distribution on a circular disk. A reflection polariscope was used to observe the surface strains from the recorded fringe patterns by digital camera. The shape of sample is a circular disk was pressed on the top and bottom and the polariscope produced fringe patterns from sample on the model being stressed. The results were analyzed, the fringe pattern looked different in various magnitude of force because the stress distribution in sample was changed with magnitude of force. Deformation can be determined from the fringe patterns.